2017
DOI: 10.1016/j.sjbs.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum trace elements and risk of preeclampsia: A case controlled study in Riyadh, Saudi Arabia

Abstract: Preeclampsia is a serious medical complication during pregnancy. In response to an increasing number of preeclamptic cases and scarcity of data concerning the interrelation between trace element levels and preeclampsia, we carried out a hospital based case-control study in Riyadh, Saudi Arabia to study the correlation between levels of serum trace elements and risk of preeclampsia. One hundred and twenty pregnant women were enrolled in this study and divided into three groups of 40 each-Control group, HR group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
1
17
1
6
Order By: Relevance
“…32 However this present study show lower serum Zn level in pregnant women than controls, and also lower Zn level in pre-eclamptic women than normal pregnant women (table 1 & 2 respectively), thus buttresses that Zn deficiency may be a major factor in the development of pre-eclampsia in this environment. This corroborates previous report from Saudi Arabia that Cu and Zn are decreased in Pre-eclampsia, 33,34 but is conflicting with a report from Iran that serum Zn in pre-eclamptics had no significant difference with normotensive subjects. 35 The present study reveals that decreases in some serum trace metals levels may in part contribute to development of pre-eclampsia in this environment.…”
Section: Discussionsupporting
confidence: 78%
“…32 However this present study show lower serum Zn level in pregnant women than controls, and also lower Zn level in pre-eclamptic women than normal pregnant women (table 1 & 2 respectively), thus buttresses that Zn deficiency may be a major factor in the development of pre-eclampsia in this environment. This corroborates previous report from Saudi Arabia that Cu and Zn are decreased in Pre-eclampsia, 33,34 but is conflicting with a report from Iran that serum Zn in pre-eclamptics had no significant difference with normotensive subjects. 35 The present study reveals that decreases in some serum trace metals levels may in part contribute to development of pre-eclampsia in this environment.…”
Section: Discussionsupporting
confidence: 78%
“…They found significant difference in serum copper level in preeclamptic patient when compare with healthy pregnant . 1,2,4,5,12 But few study show conflicting result with this study. They observed that serum copper level is higher in preeclampsia patient than normal pregnancy group.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous study showed incidence of preeclampsia in primigravida is about 10% and in multigravidae about 5%. 4 In this study, serum copper level is lower in preeclamptic patient than normal pregnant woman. This difference is highly significant (p<0.001).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Multiple studies of women of diverse ethnicities have detected significantly lower serum magnesium levels in women with preeclampsia than in women without preeclampsia. [57][58][59][60][61][62][63] Unfortunately, as with other conditions examined in this review, the analysis of serum is a major limitation of these studies, and only a few studies using analysis of red cell magnesium were found. In a small cohort (n ¼ 20 cases, n ¼ 20 controls), a significant decrease in red cell magnesium was observed in women with preeclampsia compared with controls (0.98 6 0.15 mmol/L vs 1.35 6 0.30 mmol/L, P < 0.001), which was notably not evident in the analysis of serum in the same group.…”
Section: Preeclampsiamentioning
confidence: 99%